2021
DOI: 10.1016/j.wem.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Bouldering—A Prospective Injury Evaluation

Abstract: Introduction-Bouldering has become a sport of growing interest, but little prospective evidence exists about injury proportions and patterns. The purpose of this study was to prospectively evaluate the cause of injuries sustained during indoor bouldering, proportion of affected body location, and injury severity.Methods-Proportions and patterns of injury among German-speaking indoor boulderers were evaluated prospectively in an explorative cohort study. Participants completed a baseline questionnaire assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 28 publications
(90 reference statements)
3
35
0
Order By: Relevance
“…This is supported by our present study, showing a slightly higher incidence of wrist injuries with bouldering over lead climbing. Auer et al 3 reported more acute than chronic overuse injuries from bouldering. This differs from our study in which almost 70% of the injuries were reported as chronic, with a long interval between the onset of pain and the beginning of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our present study, showing a slightly higher incidence of wrist injuries with bouldering over lead climbing. Auer et al 3 reported more acute than chronic overuse injuries from bouldering. This differs from our study in which almost 70% of the injuries were reported as chronic, with a long interval between the onset of pain and the beginning of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated injury distribution (4,(9)(10)(11). As an approximation, upper extremity injuries account for 60% to 70% of total injuries, lower extremity 20% to 30%, and others, such as head or torso injuries, less than 10%.…”
Section: Injury Epidemiologymentioning
confidence: 99%
“…1 -3 These injuries can range from acute sprains, fractures, or dislocations to chronic overuse injuries. 1 -3 Despite the high frequency of upper extremity injury among climbers, to our knowledge, acute pectoralis major tendon rupture during bouldering has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…Upper extremity injuries are common in climbing and may be seen in 25 to 90% of all climbingrelated injuries, depending on chronicity. [1][2][3] These injuries can range from acute sprains, fractures, or dislocations to chronic overuse injuries. [1][2][3] Despite the high frequency of upper extremity injury among climbers, to our knowledge, acute pectoralis major tendon rupture during bouldering has not yet been described.…”
Section: Introductionmentioning
confidence: 99%